ScrumUX: uma abordagem para integrar design de interação do usuário ao processo Scrum - Choma, Joelma (2015)
Agile development principles ensure that continuous attention to technical excellence combined with a good design contributes to increased agility ensuring products with higher quality. Usability is one of the quality attributes, and is related to making the experience enjoyable user through an efficient and intuitive interface design. Agile methods are committed to deliver valuable software to the satisfaction of the customer. At times, they deliver only the utility, without covering aspects of usability. Design solutions providing greater usability and more appropriate to the users’ context is the main concern of the Interaction Design (IxD). The IxD is based on user-centered design, which takes into account the users needs and wants, aiming to promote interaction more enjoyable experience. In recent years, the attention in integrating user-centered design practices into agile methodologies has increased. However, a very limited number of contributions have addressed the integration into a broader level, gathering practices and providing guidance to the organization of work within a software development roadmap. This dissertation presents an approach to integrate user interaction design into Scrum process through activities and artifacts. In the first stage of the study, a literature study was performed to determine possible strategies for integrating IxD into Scrum process. Furthermore, an action research approach was applied to define and evaluate the artifacts that would support the ScrumUX integration approach, closely with the professionals in the software development industry. In the second stage, an experimental study was carried out to evaluate the proposed ScrumUX integration compared to traditional Scrum approach. The experiment was carried out in an academic context, in which nineteen students divided into five teams worked in software development projects, in the ERP systems domain. Statistical tests confirmed a significant difference between the experimental and control groups, noting that the teams who used the ScrumUX approach produced software with better degree of usability in the task support perspective, considering ERP systems’ users opinion.